Exchange rate movements and their impact on trade and investment in the APEC region - Ito, Takatoshi...[et al] (IMF WashingtonUS, 1996)
Focuses on long-run movements in real exchange rates. Considers international trade and real exchange rates in the APEC region. Examines foreign direct investment and its relationship to exchange rates in the region.